2013
DOI: 10.1088/0964-1726/23/2/025017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fatigue damage in adhesively bonded lap joints through dynamic, full-spectral interrogation of fiber Bragg grating sensors: 2. Simulations

Abstract: In this paper, we simulate the response of fiber Bragg grating (FBG) sensors embedded in the adhesive layer of a composite lap that is subjected to harmonic excitation. To simulate accumulated fatigue damage at the adhesive layer, two forms of numerical nonlinearities are introduced into the model: (1) progressive plastic deformation of the adhesive and (2) changing the boundary of an interfacial defect at the adhesive layer across the overlap shear area. The simulation results are compared with previous measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Instead of directly looking for defects, there are relatively more economical techniques suitable for real-time monitoring of the integrity degradation of adhesive joints. These include strain/stiffness monitoring using back face strain gages [21][22][23], resistance monitoring of adhesive joints made conductive by adding carbon nanotubes [24,25] and optical fiber sensors signal surveillance [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Strain gages can only be applied to the outer surface, but they will disrupt an otherwise smooth surface and are susceptible to environmental degradation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead of directly looking for defects, there are relatively more economical techniques suitable for real-time monitoring of the integrity degradation of adhesive joints. These include strain/stiffness monitoring using back face strain gages [21][22][23], resistance monitoring of adhesive joints made conductive by adding carbon nanotubes [24,25] and optical fiber sensors signal surveillance [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Strain gages can only be applied to the outer surface, but they will disrupt an otherwise smooth surface and are susceptible to environmental degradation.…”
Section: Introductionmentioning
confidence: 99%
“…There are different kinds of optical fiber sensors. In adhesive joints, both the distributed sensing [29][30][31] and the discrete fiber Bragg grating (FBG) sensors have been used [8,[32][33][34][35][36][37][38][39][40][41][42][43]. The distributed sensors provide a spatially continuous strain measurement along the whole fiber and can reveal the location of any perturbation in strain caused by damages in the bond.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain measurements within the adhesive layer using FBG sensors are an increasingly common method. Various experiments have proven the applicability of the FBG technology [ 26 , 27 ]. Filigree sensors can either be embedded into the composite matrix [ 28 , 29 , 30 ] or directly into the adhesive layer [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Full-spectral response of FBGs is sensitive to the strain distribution of the gage section, that is, the spectrum is distorted by non-uniform strain, 911 and this characteristic has been applied to damage detection of the composite materials. 12 Webb et al 13,14 applied a dynamic full-spectrum FBG interrogator to a single FBG sensor embedded in the adhesive of a single-lap joint. They detected a change in the full-spectral response caused by alternation of the strain field and indicated that structural nonlinear behavior due to disbond appears in the dynamic spectral response.…”
Section: Introductionmentioning
confidence: 99%